GAME SPACE OF THE SCIENTIFIC DISCOURSE - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The problem of the space of play in the modern science is considered in the article. The idea that the game is an attribute of scientific discourse has been substantiated.